Elucidating the Translated Itawes Proverbs: A Communicational Appproach - SIplac, Grace (International Journal of Arts, Sciences and Education, 2021)
Specifically, the translation and analysis of Itawit/Itawes proverbs from Cagayan, particularly in Solana, was the subject of this research. The descriptive qualitative research approaches as well as thematic analysis were employed in this investigation. In this research, the goal is to translate Filipino proverbs into Itawes/Itawit, grasp the lessons that can be learned from each proverb, and know the specific values that may be learned from each proverb when applied to the lives of the Itawes people. According to the data, it can be stated that the Itawes proverbs convey a great deal about the Itawes as people. Aspects of the “akkahi” lives that are discussed include their interactions with others and their relationship with God. Aside from that, the researcher discovers that there are several lessons to be learned from the proverbs from the Cagayan region of the Philippines. So it is strongly advised that institutions, whether public or private educational establishments or the local government continue to promote regional proverbs by holding essay writing and poster-making contests, which can then be used as a mother tongue language during school functions. Keywords: Itawes proverbs, values, lesson, translation